(untitled) (Alternautas, 2022)
This is an article is based on the introduction to the book "Desarrollo Non Sancto. La religión como actor emergente en el debate global sobre el futuro del planeta". It discusses the role of religion as a site of discourse around the environment and sustainability, particularly in light of its historic role as an agent of social transformation. They argue that thinking about the role of religion for a socio-ecological transition can contribute to an expanded understanding of sustainability and its cultural inception, as well as its influence on daily policies, programs and practices to ensure the construction of societies capable of having a future.